CAN LEGAL TEXTS BE CULTURALLY EMBEDDED? - KOCBEK, Alenka (Comparative Legilinguistics, 2017)
In many aspects, legal translation seems to be an adequate domain for applying the principles of the functionalist approaches to translation, especially the skopos-theory by J. H. Vermeer. Nevertheless, an indiscriminate application of the principle of cultural embeddedness could prove questionable, if not misleading, as it may cause disturbance in the legal communication occurring through the translation act. In some legal transactions, such as e.g. international contracts, involving contracting parties belonging to different nations, only one legal system is adopted as the communication framework (i.e. the governing or applicable law). In such cases, the functionalist principle of cultural embeddedness needs to be applied selectively, i.e. only with respect to some linguistic features of the text, while in a broader sense, as far as the cultural and/or legal foundations of the text are concerned, the source and the target text will have the same reference frame.